To what extent could performance-based schemes help increase the effectiveness of prevention of mother-to-child transmission of HIV (PMTCT) programs in resource-limited settings? a summary of the published evidence - Dabis François; Audibert Martine; Touré Hapsatou (BMC, 2010)
Abstract Background In resource-limited settings, HIV/AIDS remains a serious threat to the social and physical well-being of women of childbearing age, pregnant women, mothers and infants. Discussion In sub-Saharan African countries with high prevalence rates, pediatric HIV/AIDS acquired through mother-to-child transmission (MTCT) can in largely be prevented by using well-established biomedical interventions. Logistical and socio-cultural barriers continue, however, to undermine the successful prevention of MTCT (PMTCT). In this paper, we review reports on maternal, neonatal and child health, as well as HIV care and treatment services that look at program incentives. Summary These studies suggest that comprehensive PMTCT strategies aiming to maximize health-worker motivation in developing countries must involve a mix of both financial and non-financial incentives. The establishment of robust ethical and regulatory standards in public-sector HIV care centers could reduce barriers to PMTCT service provision in sub-Saharan Africa and help them in achieving universal PMTCT targets.